Experimental investigation of relevant road surface descriptors for tire-road noise measurements on low-absorbing road surfaces - Pinay, Julien (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2024)
Ihrer Arbeit in der Originalsprache: This work aims at identifying relevant road surface characteristics to mitigate tire-road noise of free-rolling tires using a systematic approach. As using open porous roads is already known as an efficient measure to reduce tire rolling noise, this study will focus on compact road surfaces which have a low acoustic absorption. Measurements on standardized ISO 10844 test tracks and on public roads are used to study the norm's representativity and its completeness.